Innovative activity of Ukrainian Enterprises: challenges for Digitalization - Шейко, І. А.; Стороженко, О. В. (Львівська еономічна фундація (ЛЕФ, 2019)
Innovative development is of paramount importance in the country's economic growth, improving the economic performance of enterprises, establishing business linkages between science and education and production processes, as well as changing the structure of export and import of the country. That is why the analysis of the dynamics of the indicators of the innovation activity has paid considerable attention from scientists and specialists. In Ukrainian perspective there is a large-scale digitalization of all branches of the economy and basic spheres of life, strengthening of investments in infrastructure development, innovations and modern technologies. A case of successful digitalization of domestic machine-building enterprise is represented by state enterprise “FED” (Kharkiv)
Інноваційна активність українських підприємств: виклики цифрової економіки
Keywords: innovative development; innovative activity; digitalization; Industry 4.0; Smart Factory